The Influence of Price and Product Quality on Purchase Decisions on Thrift Clothes at Shabira Store, Tulang Bawang Regency - Safitri Malik, Annisa; Jayanti, Afrida; F Sanjaya, Vicky (Terbuka Journal of Economics and Business, 2021)
The purpose of this study was to determine the effect of price and product quality on purchasing decisions. The subject used in this study is a picture of a secondhand shop from the Shabira Store, Tulang Bawang Regency. The method used is a questionnaire instrument, the sample used is consumers at the Shabira Store, Tulang Bawang Regency, totaling 66 respondents. The statistical test used is PLS-based Structural Equation Modeling. Validity test using Factor Loading then Reliability Test using Cronbach'c Alpha, Composite Reliability and Average Variance Extracted (AVE) values. Thus, all the results of the index items used in this study are valid and reliable, thus